Digital Development: Reimagining Research Beyond ICT4D - Sahay, Sundeep; Srivastava, Shirish C.; Barrett, Michael; Davison, Robert M.; Madon, Shirin; Schlagwein, Daniel; Brown, Irwin; Sarker, Suprateek (Information Systems Research, 2025)
This editorial introduces a conceptual framework that reimagines research on Information and Communication Technologies for Development (ICT4D) as “digital development,” recognizing the inseparable intertwining of digital and development trajectories. This framing is aimed at the broader information systems (IS) research community, which includes ICT4D researchers, based both in the Global South and the Global North. Digital development encompasses three dimensions: digital in development (institutional use), digital for development (conscious design for outcomes), and development in a digital world (digital entanglement in development practice.). We argue that this reimagination is necessary for three reasons. First, digital technologies are becoming increasingly entangled with many development initiatives, implying the need to be studied as a duality, not a dualism. Second, we are witnessing the rising complexity of contemporary and emergent development challenges, which are not just limited to the Global South, but to the world at large. Third, the IS and ICT4D research fields have long worked in relative isolation from each other, but they need to synergistically create new theories and methods to address the rising complexities inherent in the “digital” and “development.” We provide a brief overview of the existing ICT4D field to identify critical areas for reconceptualization and expansion. This is then illustrated by examples from four empirical domains, namely humanitarian governance, global health, financial inclusion, and digital nomadism, which are representative of contemporary and emerging digital development challenges. This leads to the development of theoretical, policy and practice, and methodological implications, which provide a basis to formulate a research agenda for digital development.